Quantum dynamics, chaos and thermalization - Fine, B.V. (Nazarbayev University, 2013)
Should one investigate the detailed properties of microscopic chaos in systems of many classical particles, even though one knows that the real macroscopic systems are made of quantum particles? Should one investigate statistical ensembles that admit superpositions of macroscopically distinct quantum states, even though such superpositions have not yet been observed in Nature? Our answer to both of these questions is yes. Regarding the first question, our work indicates that there is still a lot to learn about the properties of many-particle quantum systems from the detailed studies of many-particle classical systems. Regarding the second question, one needs to take the linear quantum mechanics to its limit in order to discover the range of validity of quantum statistical physics. The fact that the Gibbs equilibrium is overwhelmingly supported by experiments does not necessarily suggest that there exist a self-contained justification for excluding macroscopically distinct superpositions in the framework of purely linear quantum mechanics. In a typical experiment, macroscopic quantum systems are being continuously “monitored” by the environment.
Keywords: first research week; quantum dynamics; thermalization; statistical physics